APPLICATION MODEL AS ONLINE TICKETING AND FUNDING PLATFORM FOR MOBILE-BASED CULTURAL EVENTS - Adie Wahyudi Oktavia Gama; John Junieargo Timotius; I Gusti Ngurah Darma Paramartha; I Wayan Aditya Suranata (Jurnal Mantik, 2022)
The Covid-19 pandemic has had an impact on cultural tourism actors in Indonesia having difficulty holding their cultural events again due to financial constraints. And ticket sales are still conventional. The research technique used is descriptive analysis method with literature study. The data collection technique used is literature study. And the software development technique used is the Software Development Life Cycle method with a prototype development model. The results of this research are in the form of a mobile application model that combines two functions, namely as an online ticketing platform and a funding platform, into one complete system that is interconnected with each other. Design design using Adobe Xd tools. Applications can CRUD data from and to the cloud server using the REST API. The cloud server used is Firestore, while the REST API uses Firebase Functions developed with the Javascript programming language (NodeJs) through the Firebase CLI. And also the application runs tests with unit testing, instrumentation testing, and performance testing with good results. Based on the results of this study, it can be concluded that the model or application design resulting from this research is a mobile application that has met the Minimum Viable Product (MVP) with an APK format that runs on the Android operating system, namely the native app. Along with other features and specifications described in this paper.